PNEUMONIA IN CHILDREN WITH CONGENITAL HEART DISEASE: CLINICAL CHALLENGES AND MANAGEMENT STRATEGIES - Javlon Mamanazirov (Western European Studies, 2025)
Pneumonia remains a leading cause of morbidity and mortality in children, with those having congenital heart disease (CHD) being particularly vulnerable. The presence of underlying structural heart defects complicates the disease course, increasing the risk of severe infections, prolonged hospital stays, and higher mortality rates. This article explores the epidemiology, pathophysiology, risk factors, diagnostic challenges, and management strategies for pneumonia in children with CHD. Evidence-based approaches to antibiotic use, preventive measures, and long-term outcomes are discussed to improve clinical care and patient prognosis.
Keywords: Pneumonia; congenital heart disease; pediatric infections